A rapid MALDI‐TOF mass spectrometry‐based method for colistin susceptibility testing in Escherichia coli. Issue 2 (20th May 2021) - Li, Jiaping; Huang, Yonglu; Hu, Yanyan; Sun, Qiaoling; Cai, Jiachang; Zhou, Hongwei; Gu, Danxia; Chen, Gongxiang; Wang, Yang; Zhang, Rong
Summary: Colistin is recognized as a last‐resort treatment option against multi‐drug resistant bacteria including carbapenem‐resistant Enterobacteriaceae (CRE). However, the plasmid‐mediated colistin‐resistance gene mcr‐1 has been reported globally resulting in an increase of colistin‐resistant bacteria. A quick and accurate method for determining the pathogen resistance of colistin is therefore crucial in the clinic. Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) is a potential tool forto be applied for antimicrobial susceptibility testing. We compared the growth of Escherichia coli strains in the presence or absence of colistin. Automated analyses of the spectra were performed with a prototype software tool written with package R. Three mcr‐1 ‐positive and six mcr‐1‐ negative E. coli were used for establishing the model to obtain the optimal incubation time, the breakpoint concentration of colistin and cut‐off of the relative growth (RG) value. The distinction between susceptible and resistant strains was already noticeable after 2 h of incubation. The best separation between the susceptible and resistant strains was achieved at a concentration of 4 µg ml ‐1 and a relative growth cut‐off value of 0.6. Application of the model for the analysis of 128 E . coli isolates, a sensitivity of 97.4% and a specificity of 88.2% were achieved compared with colistin MIC results. The rapid MALDI‐TOF MS‐based method approach is simple to set‐up, uses a short incubation time, and had excellent outcomes with respect to sensitivity and specificity for colistin sensitivity testing in Escherichia coli . Abstract : The rapid MALDI‐TOF MS‐based method approach is simple to setup, uses a short incubation time, and had excellent outcomes with respect to sensitivity and specificity for colistin sensitivity testing in Escherichia coli . The MS‐methods we developed will facilitate the fast diagnosis of colistin‐resistance in clinical practice.